Model Pembelajaran Tutorial Berbantuan Media Komputer terhadap Hasil Belajar TIK Siswa Kelas V di SD Jembatan Budaya Badung - Dewi, Ni Kadek Yuliana Sintya; Yudana, I Made; Dantes, Kadek Rihendra (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The problem of this research is the low ICT learning outcomes of learners. This study aims to determine the differences in ICT learning outcomes before and after the application of computer-assisted tutorial learning models and the influence of these learning models on ICT learning outcomes. This type of research is quasi-experimental. The population of this study was all grade 5 students, with a sample of 2 classes, namely 5C as the experimental class and 5E as the control class. Data collection using objective tests. Data analysis uses descriptive statistical analysis and inferential statistical analysis. The results showed that (1) in the pretest obtained t-count (1.77) < t-table (2.00) meaning that there was no difference in ICT learning outcomes before the application of the computer-assisted tutorial learning model, (2) in the postest obtained t-count (6.68) > t-table (2.00) meaning that there were differences in ICT learning outcomes after the application of the computer-assisted tutorial learning model, (3) based on the results of N gain score and t-test obtained t-count (2.349) > t-table (2.015) This means that there is a significant influence of computer-assisted tutorial learning models on improving ICT learning outcomes by 71%, including in the high category. It was concluded that this learning model was quite effective in improving ICT learning outcomes of grade 5 students of SD Jembatan Budaya Badung.